Stage specific activity of synthetic antimalarial endoperoxides, N-89 and N-251, against Plasmodium falciparum. Issue 1 (February 2015) - Morita, Masayuki; Koyama, Takahiko; Sanai, Hitomi; Sato, Akira; Hiramoto, Akiko; Masuyama, Araki; Nojima, Masatomo; Wataya, Yusuke; Kim, Hye-Sook
Abstract We have reported that two endoperoxides, N-89 and N-251, synthesized in 2001, possess potent antimalarial activities. Aiming at their eventual use for curing malaria in humans, we have been investigating various aspects of their antimalarial actions. Here we show that N-89 and N-251 inhibit the growth of Plasmodium falciparum within human erythrocytes in vitro at its lifecycle stage 'trophozoite' specifically. It is known that artemisinin compounds, which are currently used for curing malaria, have other stage-specificities. Therefore, it is likely that the antimalarial mechanism of N-89 and N-251 differs from those of artemisinin compounds. As malaria parasites resistant to artemisinin-based combination therapy are currently emerging in some tropical regions, N-89 and N-251 are candidates for overcoming these new problems.